High-pressure structural phase transition and metallization in Ga2S3 under non-hydrostatic and hydrostatic conditions up to 36.4 GPa. Issue 8 (4th February 2021) - Yang, Linfei; Jiang, Jianjun; Dai, Lidong; Hu, Haiying; Hong, Meiling; Zhang, Xinyu; Li, Heping; Liu, Pengfei
Abstract : The vibrational, electrical and structural properties of Ga2 S3 were explored by Raman spectroscopy, EC measurements, HRTEM and First-principles theoretical calculations under different pressure environments up to 36.4 GPa. Abstract : The vibrational, electrical and structural properties of gallium sulfide (Ga2 S3 ) were explored by Raman spectroscopy, electrical conductivity measurements, high-resolution transmission electron microscopy and first-principles theoretical calculations under different pressure environments up to 36.4 GPa. Upon compression, Ga2 S3 underwent a first-order structural phase transition accompanied by a semiconductor-to-metal transformation at 17.2 GPa under non-hydrostatic conditions, whereas, the transition occurred at a much lower pressure of 11.3 GPa under hydrostatic conditions because of the influence of the pressure medium. Upon decompression, two possible new high-pressure polymorphs were observed at 8.0 and 3.0 GPa under non-hydrostatic conditions, and similar transition points were obtained under hydrostatic conditions. The structural and electrical transport evolution for Ga2 S3 upon compression and decompression can help us to deeply understand the high-pressure behaviors of other similar A2 B3 -type structural compounds.